2016
DOI: 10.1038/srep30131
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear force dependence on optically bound micro-particle arrays in the evanescent fields of fundamental and higher order microfibre modes

Abstract: Particles trapped in the evanescent field of an ultrathin optical fibre interact over very long distances via multiple scattering of the fibre-guided fields. In ultrathin fibres that support higher order modes, these interactions are stronger and exhibit qualitatively new behaviour due to the coupling of different fibre modes, which have different propagation wave-vectors, by the particles. Here, we study one dimensional longitudinal optical binding interactions of chains of 3 μm polystyrene spheres under the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…In the case of a single or a few particles a detailed numerical modeling of the setup is possible with good agreement to the experiment. However, as shown recently, the key physics can be already modeled and understood from a much simplified semi-analytical scattering model [15]. We will generalize this model here towards multifrequency illumination and extract the key physics originating from frequency control.…”
Section: Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…In the case of a single or a few particles a detailed numerical modeling of the setup is possible with good agreement to the experiment. However, as shown recently, the key physics can be already modeled and understood from a much simplified semi-analytical scattering model [15]. We will generalize this model here towards multifrequency illumination and extract the key physics originating from frequency control.…”
Section: Modelmentioning
confidence: 94%
“…In this work we consider broadband transverse illumination characterized by the intensities, central frequencies and spectral widths of the incoming beams. of the particles [15], which will give upper limits on the possible illumination powers, but generally do not seriously affect the longitudinal dynamics.…”
Section: Modelmentioning
confidence: 99%
“…Previous studies had demonstrated multiple miniature fiber lasers using rare-earth doped microfibers [10][11][12]. On the other hand, higher order transverse modes with more complex modal properties offer additional dimension of freedom to manipulate optical field for various applications, and thus have attracted wide interest on relevant topics ranging from propagation characteristics [13,14], selective mode excitation/conversion [15,16] to particle trapping [17,18], higher order mode lasers [19,20], optical vortex generation [21,22] and so on. To inspect fiber modes, one common method is direct imaging of modal profiles at a fiber's output end.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches have been investigated heretofore (8). The first one consists in using the light propagating in a waveguide to trap and propel particles as on a conveyor belt (4,5,(9)(10)(11)(12)(13)(14)(15)(16). However, this strategy usually fails whenever trapped particles' propulsion has to be stopped, requiring more complex and restrictive implementation based on irregular waveguide geometries (17), microfluidic channel walls (18), or counter-propagating modes (8,(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%